Review on nanoparticles and nanostructured materials: history, sources, toxicity and regulations - Jeevanandam, Jaison; Barhoum, Ahmed; Chan, Yen S.; Dufresne, Alain; Danquah, Michael K. (Beilstein Journal of Nanotechnology, 2018)
Nanomaterials (NMs) have gained prominence in technological advancements due to their tunable physical, chemical and biological properties with enhanced performance over their bulk counterparts. NMs are categorized depending on their size, composition, shape, and origin. The ability to predict the unique properties of NMs increases the value of each classification. Due to increased growth of production of NMs and their industrial applications, issues relating to toxicity are inevitable. The aim of this review is to compare synthetic (engineered) and naturally occurring nanoparticles (NPs) and nanostructured materials (NSMs) to identify their nanoscale properties and to define the specific knowledge gaps related to the risk assessment of NPs and NSMs in the environment. The review presents an overview of the history and classifications of NMs and gives an overview of the various sources of NPs and NSMs, from natural to synthetic, and their toxic effects towards mammalian cells and tissue. Additionally, the types of toxic reactions associated with NPs and NSMs and the regulations implemented by different countries to reduce the associated risks are also discussed.
Keywords: nanomaterial classification; nanomaterial history; nanotoxicity; oxidative stress; reactive oxygen species; regulations

(untitled) - Boverhof, D. R.; Bramante, C. M.; Butala, J. H.; Clancy, S. F.; Lafranconi, M.; West, J.; Gordon, S. C. (Regul. Toxicol. Pharmacol., 2015)

Questions About Nanotechnology - United Nations (2012)

Considering Whether an FDA-Regulated Product Involves the Application of Nanotechnology (Federal Drug Administration, 2011)

ISO/TS 80004-1:2010, Nanotechnology – Vocabulary – Part 1: Core Terms (International Organization for Standardization, 2010)

Interpretation and implications of the European Commission's definition on nanomaterials; Letter report 601358001 - Bleeker, E. A. J.; Cassee, F. R.; Geertsma, R. E.; de Jong, W. H.; Heugens, E. H. W.; Koers-Jacquemijns, M.; van De Meent, D.; Oomen, A. G.; Popma, J.; Rietveld, A. G.; Wijnhoven, S. W. P. (RIVM, 2012)
https://www.rivm.nl/bibliotheek/rapporten/601358001.html

(untitled) - Potocnik, J. (Off. J. Eur. Communities: Legis., 2011)

PAS 71:2011, Nanoparticles. Vocabulary (British Standards Institution, 2011)

Essentials in Nanoscience and Nanotechnology - Kumar, N.; Kumbhat, S. (Carbon-Based Nanomaterials, 2016)

(untitled) - Zhang, L.; Wang, L.; Jiang, Z.; Xie, Z. (Nanoscale Res. Lett., 2012)

(untitled) - Pan, D.; Wang, Q.; An, L. (J. Mater. Chem., 2009)

(untitled) - Li, C.; Adamcik, J.; Mezzenga, R. (Nat. Nanotechnol., 2012)

(untitled) - Zhang, J.; Langille, M. R.; Mirkin, C. A. (Nano Lett., 2011)

(untitled) - Badrossamay, M. R.; McIlwee, H. A.; Goss, J. A.; Parker, K. K. (Nano Lett., 2010)

(untitled) - Gokarna, A.; Parize, R.; Kadiri, H.; Nomenyo, K.; Patriarche, G.; Miska, P.; Lerondel, G. (RSC Adv., 2014)

(untitled) - Zhou, J.; Ding, Y.; Deng, S. Z.; Gong, L.; Xu, N. S.; Wang, Z. L. (Adv. Mater., 2005)

(untitled) - Gleiter, H. (Acta Mater., 2000)

(untitled) - Tiwari, J. N.; Tiwari, R. N.; Kim, K. S. (Prog. Mater. Sci., 2012)

(untitled) - Pokropivny, V. V.; Skorokhod, V. V. (Mater. Sci. Eng., C, 2007)

(untitled) - Hochella, M. F., Jr; Spencer, M. G.; Jones, K. L. (Environ. Sci.: Nano, 2015)

(untitled) - Sharma, V. K.; Filip, J.; Zboril, R.; Varma, R. S. (Chem. Soc. Rev., 2015)

(untitled) - Wagner, S.; Gondikas, A.; Neubauer, E.; Hofmann, T.; von der Kammer, F. (Angew. Chem., Int. Ed., 2014)

(untitled) - Heiligtag, F. J.; Niederberger, M. (Mater. Today, 2013)

(untitled) - Walter, P.; Welcomme, E.; Hallégot, P.; Zaluzec, N. J.; Deeb, C.; Castaing, J.; Veyssière, P.; Bréniaux, R.; Lévêque, J.-L.; Tsoucaris, G. (Nano Lett., 2006)

(untitled) - Johnson-McDaniel, D.; Barrett, C. A.; Sharafi, A.; Salguero, T. T. (J. Am. Ceram. Soc., 2013)

(untitled) - Schaming, D.; Remita, H. (Found Chem., 2015)

(untitled) - Artioli, G.; Angelini, I.; Polla, A. (Phase Transitions, 2008)

(untitled) - Brun, N.; Mazerolles, L.; Pernot, M. (J. Mater. Sci. Lett., 1991)

(untitled) - Leonhardt, U. (Nat. Photonics, 2007)

(untitled) - Freestone, I.; Meeks, N.; Sax, M.; Higgitt, C. (Gold Bull., 2007)

(untitled) - Nakai, I.; Numako, C.; Hosono, H.; Yamasaki, K. (J. Am. Ceram. Soc., 1999)

(untitled) - Rytwo, G. (La revista Macla, 2008)

(untitled) - Mie, G. (Ann. Phys. (Berlin, Ger.), 1908)

(untitled) - Rittner, M. N.; Abraham, T. (JOM, 1998)

Samsung and its attractions - Asia's new model company (London, United Kingdom, 2011)

Benefits, Risks, Ethical, Legal and Social Aspects of Nanotechnology (nanoforum.org, European Nanotechnology Gateway, 2004)
2nd edition, October 2005.

(untitled) - Alexiou, C.; Arnold, W.; Hulin, P.; Klein, R.; Schmidt, A.; Bergemann, C.; Parak, F. G. (Magnetohydrodynamics, 2001)

(untitled) - Odenbach, S. (Colloids Surf., A, 2003)

(untitled) - Déry, J.-P.; Borra, E. F.; Ritcey, A. M. (Chem. Mater., 2008)

Morphing mirror could clear the skies for astronomers (London, United Kingdom, 2008)

(untitled) - O’Regan, B.; Grätzel, M. (Nature, 1991)

(untitled) - Kreuter, J. (Int. J. Pharm., 2007)

(untitled) - Vance, M. E.; Kuiken, T.; Vejerano, E. P.; McGinnis, S. P.; Hochella, M. F., Jr; Rejeski, D.; Hull, M. S. (Beilstein J. Nanotechnol., 2015)

(untitled) - Taylor, D. A. (Environ. Health Perspect., 2002)

Nature's Nanostructures - Barnard, A. S.; Guo, H. (Pan Stanford Publishing, 2012)

(untitled) - Dai, Z. R.; Bradley, J. P.; Joswiak, D. J.; Brownlee, D. E.; Hill, H. G. M.; Genge, M. J. (Nature, 2002)

(untitled) - d'Almeida, G. A.; Schütz, L. (J. Clim. Appl. Meteorol., 1983)

(untitled) - Shi, Z.; Shao, L.; Jones, T. P.; Lu, S. (J. Geophys. Res.: Atmos., 2005)

(untitled) - Buseck, P. R.; Pósfai, M. (Proc. Natl. Acad. Sci. U. S. A., 1999)

(untitled) - Al-Dabbous, A. N.; Kumar, P. (Environ. Sci. Technol., 2014)

(untitled) - Sapkota, A.; Symons, J. M.; Kleissl, J.; Wang, L.; Parlange, M. B.; Ondov, J.; Breysse, P. N.; Diette, G. B.; Eggleston, P. A.; Buckley, T. J. (Environ. Sci. Technol., 2005)

Bionano frontier - Ankamwar, B. (Nanotechnology's environmental impact, 2012)

(untitled) - Husar, R. B.; Tratt, D. M.; Schichtel, B. A.; Falke, S. R.; Li, F.; Jaffe, D.; Gassó, S.; Gill, T.; Laulainen, N. S.; Lu, F.; Reheis, M. C.; Chun, Y.; et al. (J. Geophys. Res.: Atmos., 2001)

(untitled) - McKendry, I. G.; Hacker, J. P.; Stull, R.; Sakiyama, S.; Mignacca, D.; Reid, K. (J. Geophys. Res.: Atmos., 2001)

(untitled) - Shi, Z.; Krom, M. D.; Bonneville, S.; Baker, A. R.; Jickells, T. D.; Benning, L. G. (Environ. Sci. Technol., 2009)

(untitled) - Zhuang, G.; Yii, Z.; Duce, R. A.; Brown, P. R. (Nature, 1992)

(untitled) - Meskhidze, N.; Chameides, W. L.; Nenes, A. (J. Geophys. Res.: Atmos., 2005)

(untitled) - Solmon, F.; Chuang, P. Y.; Meskhidze, N.; Chen, Y. (J. Geophys. Res.: Atmos., 2009)

NASA to detail plans today for trip to moon: research has started for extensive journeys (2005)

Apollo 17 Mission (2016)

Proceedings of the 1st Space Exploration Conference: Continuing the Voyage of Discovery, Space Exploration Conferences - Taylor, L.; Schmitt, H.; Carrier, W.; Nakagawa, M. (Lunar Dust Problem: From Liability to Asset, 30.1.2005-1.2.2005, 2005)

Don't Breathe the Moondust (2005)

(untitled) - Batsura, Yu. D.; Kruglikov, G. G.; Arutiunov, V. D. (Bull. Exp. Biol. Med., 1981)

En Route to Mars, The Moon (2005)

(untitled) - Buzea, C.; Pacheco, I. I.; Robbie, K. (Biointerphases, 2007)

(untitled) - Ammann, M.; Burtscher, H. (Bull. Volcanol., 1990)

(untitled) - Meeker, K. A.; Chuan, R. L.; Kyle, P. R.; Palais, J. M. (Geophys. Res. Lett., 1991)

(untitled) - Guo, S.; Bluth, G. J. S.; Rose, W. I.; Watson, I. M. (Geochem., Geophys., Geosyst., 2004)

(untitled) - Rietmeijer, F. J. M.; Mackinnon, I. D. R. (J. Geophys. Res.: Planets, 1997)

(untitled) - Yano, E.; Yokoyama, Y.; Higashi, H.; Nishii, S.; Maeda, K.; Koizumi, A. (Arch. Environ. Health, 1990)

(untitled) - Blundell, G.; Henderson, W. J.; Price, E. W. (Ann. Trop. Med. Parasitol., 1989)

(untitled) - Corachán, M. (Med. Clin. (Barcelona), 1988)

(untitled) - Corachán, M.; Tura, J. M.; Campo, E.; Soley, M.; Traveria, A. (Trop. Geogr. Med., 1988)

(untitled) - Mott, J. A.; Meyer, P.; Mannino, D.; Redd, S. C. (West. J. Med., 2002)

(untitled) - Montella, M.; Franceschi, S.; Geddes da Filicaia, M.; De Macro, M.; Arniani, S.; Balzi, D.; Delfino, M.; Lannuzzo, M.; Buonanno, M.; Satriano, R. A. (Epidemiologia e Prevenzione, 1997)

(untitled) - Fuller, L. C. (Curr. Opin. Infect. Dis., 2005)

(untitled) - Gustafsson, Ö.; Kruså, M.; Zencak, Z.; Sheesley, R. J.; Granat, L.; Engström, E.; Praveen, P. S.; Rao, P. S. P.; Leck, C.; Rodhe, H. (Science, 2009)

(untitled) - Smita, S.; Gupta, S. K.; Bartonova, A.; Dusinska, M.; Gutleb, A. C.; Rahman, Q. (Gut, 2012)

(untitled) - Duck, T. J.; Firanski, B. J.; Millet, D. B.; Goldstein, A. H.; Allan, J.; Holzinger, R.; Worsnop, D. R.; White, A. B.; Stohl, A.; Dickinson, C. S.; van Donkelaar, A. (J. Geophys. Res.: Atmos., 2007)

Wildfire smoke causes air quality to worsen in TN, SC, and NC (2016)

(untitled) - Buseck, P. R.; Adachi, K. (Elements, 2008)

SEAWIFS: Lake Michigan Brightens again (2001)

(untitled) - Pósfai, M.; Simonics, R.; Li, J.; Hobbs, P. V.; Buseck, P. R. (J. Geophys. Res.: Atmos., 2003)

(untitled) - Linak, W. P.; Miller, C. A.; Wendt, J. O. L. (J. Air Waste Manage. Assoc., 2000)

(untitled) - Rogers, F.; Arnott, P.; Zielinska, B.; Sagebiel, J.; Kelly, K. E.; Wagner, D.; Lighty, J. S.; Sarofim, A. F. (J. Air Waste Manage. Assoc., 2005)

(untitled) - De Volder, M. F. L.; Tawfick, S. H.; Baughman, R. H.; Hart, A. J. (Science, 2013)

(untitled) - Weir, A.; Westerhoff, P.; Fabricius, L.; Hristovski, K.; Von Goetz, N. (Environ. Sci. Technol., 2012)

(untitled) - Sadat-Shojai, M.; Atai, M.; Nodehi, A.; Khanlar, L. N. (Dent. Mater., 2010)

(untitled) - Kagawa, J. (Toxicology, 2002)

(untitled) - Westerdahl, D.; Fruin, S.; Sax, T.; Fine, P. M.; Sioutas, C. (Atmos. Environ., 2005)

(untitled) - Sioutas, C.; Delfino, R. J.; Singh, M. (Environ. Health Perspect., 2005)

(untitled) - Soto, K. F.; Carrasco, A.; Powell, T. G.; Garza, K. M.; Murr, L. E. (J. Nanopart. Res., 2005)

Abstracts of Current Research on Diesel Exhaust Particles: Meeting of the Japan Association of Aerosol Science and Technology - Kittelson, D. (Recent measurements of nanoparticle emissions from engines, Tokyo, Japan, 2001)

(untitled) - Singh, M.; Phuleria, H. C.; Bowers, K.; Sioutas, C. (J. Exposure Sci. Environ. Epidemiol., 2006)

(untitled) - Donaldson, K.; Stone, V. (Ann. Ist. Super. Sanita, 2003)

(untitled) - Kolosnjaj-Tabi, J.; Just, J.; Hartman, K. B.; Laoudi, Y.; Boudjemaa, S.; Alloyeau, D.; Szwarc, H.; Wilson, L. J.; Moussa, F. (EBioMedicine, 2015)

(untitled) - Penn, A.; Murphy, G.; Barker, S.; Henk, W.; Penn, L. (Environ. Health Perspect., 2005)

(untitled) - Vermylen, J.; Nemmar, A.; Nemery, B.; Hoylaerts, M. F. (J. Thromb. Haemostasis, 2005)

(untitled) - Hoek, G.; Brunekreef, B.; Goldbohm, S.; Fischer, P.; van den Brandt, P. A. (Lancet, 2002)

(untitled) - Knox, E. G. (Br. J. Prev. Soc. Med., 2005)

(untitled) - Bigert, C.; Gustavsson, P.; Hallqvist, J.; Hogstedt, C.; Lewné, M.; Plato, N.; Reuterwall, C.; Schéele, P. (Epidemiology, 2003)

(untitled) - Riediker, M.; Devlin, R. B.; Griggs, T. R.; Herbst, M. C.; Bromberg, P. A.; Williams, R. W.; Cascio, W. E. (Part. Fibre Toxicol., 2004)

(untitled) - Ning, Z.; Cheung, C. S.; Fu, J.; Liu, M. A.; Schnell, M. A. (Sci. Total Environ., 2006)

(untitled) - Stefani, D.; Wardman, D.; Lambert, T. (J. Air Waste Manage. Assoc., 2005)

(untitled) - Rushton, L. (Rev. Environ. Health, 2004)

(untitled) - Husgafvel-Pursiainen, K. (Mutat. Res., Rev. Mutat. Res., 2004)

(untitled) - Godtfredsen, N. S.; Osler, M.; Vestbo, J.; Andersen, I.; Prescott, E. (J. Epidemiol. Community Health, 2003)

(untitled) - Fireman, E. M.; Lerman, Y.; Ganor, E.; Greif, J.; Fireman-Shoresh, S.; Lioy, P. J.; Banauch, G. I.; Weiden, M.; Kelly, K. J.; Prezant, D. J. (Environ. Health Perspect., 2004)

(untitled) - Xiao, L.; Takada, H.; Maeda, K.; Haramoto, M.; Miwa, N. (Biomed. Pharmacother., 2005)

(untitled) - Monteiro-Riviere, N. A.; Wiench, K.; Landsiedel, R.; Schulte, S.; Inman, A. O.; Riviere, J. E. (Toxicol. Sci., 2011)

Synthesis, properties and applications - Cao, G. (World Scientific, 2004)

(untitled) - Hyeon, T. (Chem. Commun., 2003)

(untitled) - Mohanpuria, P.; Rana, N. K.; Yadav, S. K. (J. Nanopart. Res., 2008)

Nano-particles in baby formula: Tiny new ingredients are a big concern (2016)

(untitled) - Donaldson, K.; Stone, V.; Tran, C. L.; Kreyling, W.; Borm, P. J. A. (Occup. Environ. Med., 2004)

Inventory Finds Increase in Consumer Products Containing Nanoscale Materials (2013)

(untitled) - de Lima, R.; Seabra, A. B.; Durán, N. (J. Appl. Toxicol., 2012)

Nanotoxicology - Durán, N.; Seabra, A. B.; de Lima, R. (Cytotoxicity and genotoxicity of biogenically synthesized silver nanoparticles, 2014)

(untitled) - Skalska, J.; Strużyńska, L. (Folia Neuropathol., 2015)

(untitled) - Heydarnejad, M. S.; Samani, R. J. (J. Nanomed. Nanotechnol., 2016)

(untitled) - Ema, M.; Okuda, H.; Gamo, M.; Honda, K. (Reprod. Toxicol., 2017)

(untitled) - Duckworth, D. H.; Gulig, P. A. (BioDrugs, 2002)

(untitled) - Picó, B.; Díez, M. J.; Nuez, F. (Sci. Hortic. (Amsterdam, Neth.), 1996)

(untitled) - Berg, T. P. V. D. (Avian Pathol., 2000)

(untitled) - Uchiyama, T. (Annu. Rev. Immunol., 1997)

(untitled) - Flenniken, M. L.; Willits, D. A.; Brumfield, S.; Young, M. J.; Douglas, T. (Nano Lett., 2003)

(untitled) - Flenniken, M. L.; Willits, D. A.; Harmsen, A. L.; Liepold, L. O.; Harmsen, A. G.; Young, M. J.; Douglas, T. (Chem. Biol., 2006)

Viruses and Nanotechnology - Strable, E.; Finn, M. G. (Chemical modification of viruses and virus-like particles, 2009)

(untitled) - Saunders, K.; Sainsbury, F.; Lomonossoff, G. P. (Virology, 2009)

(untitled) - Langeveld, J. P. M.; Brennan, F. R.; Martínez-Torrecuadrada, J. L.; Jones, T. D.; Boshuizen, R. S.; Vela, C.; Casal, J. I.; Kamstrup, S.; Dalsgaard, K.; Meloen, R. H.; Bendig, M. M.; Hamilton, W. D. O. (Vaccine, 2001)

(untitled) - Wang, Q.; Lin, T.; Tang, L.; Johnson, J. E.; Finn, M. G. (Angew. Chem., Int. Ed., 2002)

(untitled) - Douglas, T.; Young, M. (Nature, 1998)

(untitled) - Ren, Y.; Wong, S.-M.; Lim, L.-Y. (J. Gen. Virol., 2006)

(untitled) - Singh, P.; Prasuhn, D.; Yeh, R. M.; Destito, G.; Rae, C. S.; Osborn, K.; Finn, M. G.; Manchester, M. (J. Controlled Release, 2007)

Application of HCRSV protein cage for anticancer drug delivery - Yupeng, R. (National University of Singapore, 2007)

The transmission electron microscope - Theory and application - Catroxo, M. H. B.; Martins, A. M. C. R. P. F. (Veterinary diagnostic using transmission electron microscopy, 2015)

(untitled) - Alphandéry, E. (Front. Bioeng. Biotechnol., 2014)

(untitled) - Southam, G.; Donald, R. (Earth-Sci. Rev., 1999)

(untitled) - Haefeli, C.; Franklin, C.; Hardy, K. (J. Bacteriol., 1984)

Encyclopedia of nanoscience and nanotechnology - Slocik, J. M.; Knecht, M. R.; Wright, D. W. (Biogenic nanoparticles, 2004)

(untitled) - Nair, B.; Pradeep, T. (Cryst. Growth Des., 2002)

(untitled) - Senapati, S.; Ahmad, A.; Khan, M. I.; Sastry, M.; Kumar, R. (Small, 2005)

(untitled) - Zheng, D.; Hu, C.; Gan, T.; Dang, X.; Hu, S. (Sens. Actuators, B, 2010)

(untitled) - Jha, A. K.; Prasad, K.; Prasad, K. (Biochem. Eng. J., 2009)

(untitled) - Jha, A. K.; Prasad, K. (Colloids Surf., B, 2010)

(untitled) - Jha, A. K.; Prasad, K.; Kulkarni, A. R. (Colloids Surf., B, 2009)

(untitled) - Bansal, V.; Poddar, P.; Ahmad, A.; Sastry, M. (J. Am. Ceram. Soc., 2006)

(untitled) - Narayanan, K. B.; Sakthivel, N. (Adv. Colloid Interface Sci., 2010)

(untitled) - Sweeney, R. Y.; Mao, C.; Gao, X.; Burt, J. L.; Belcher, A. M.; Georgiou, G.; Iverson, B. L. (Chem. Biol., 2004)

(untitled) - Mandal, D.; Bolander, M. E.; Mukhopadhyay, D.; Sarkar, G.; Mukherjee, P. (Appl. Microbiol. Biotechnol., 2006)

(untitled) - Labrenz, M.; Druschel, G. K.; Thomsen-Ebert, T.; Gilbert, B.; Welch, S. A.; Kemner, K. M.; Logan, G. A.; Summons, R. E.; De Stasio, G.; Bond, P. L.; Lai, B.; Kelly, S. D.; et al. (Science, 2000)

(untitled) - Ahmad, A.; Senapati, S.; Khan, M. I.; Kumar, R.; Sastry, M. (Langmuir, 2003)

(untitled) - Li, X.; Xu, H.; Chen, Z.-S.; Chen, G. (J. Nanomater., 2011)

(untitled) - Jeevanandam, J.; Chan, Y. S.; Danquah, M. K. (ChemBioEng Rev., 2016)

(untitled) - Uwins, P. J. R.; Webb, R. I.; Taylor, A. P. (Am. Mineral., 1998)

Australian Petroleum Production and Exploration Association Conference - Urwins, P. (Novel nano-organisms (nanobes): Living analogues for Martian "nanobacteria"?, 2000)

(untitled) - Bazylinski, D. A.; Garratt-Reed, A. J.; Frankel, R. B. (Microsc. Res. Tech., 1994)

(untitled) - Bazylinski, D. A.; Frankel, R. B.; Heywood, B. R.; Mann, S.; King, J. W.; Donaghay, P. L.; Hanson, A. K. (Appl. Environ. Microbiol., 1995)

(untitled) - Fan, T.-X.; Chow, S.-K.; Zhang, D. (Prog. Mater. Sci., 2009)

(untitled) - Watson, J. H. P.; Ellwood, D. C.; Soper, A. K.; Charnock, J. (J. Magn. Magn. Mater., 1999)

(untitled) - Zhang, C.; Vali, H.; Romanek, C. S.; Phelps, T. J.; Liu, S. V. (Am. Mineral., 1998)

(untitled) - Roh, Y.; Lauf, R. J.; McMillan, A. D.; Zhang, C.; Rawn, C. J.; Bai, J.; Phelps, T. J. (Solid State Commun., 2001)

(untitled) - Philipse, A. P.; Maas, D. (Langmuir, 2002)

(untitled) - Lee, H.; Purdon, A. M.; Chu, V.; Westervelt, R. M. (Nano Lett., 2004)

(untitled) - Arakaki, A.; Nakazawa, H.; Nemoto, M.; Mori, T.; Matsunaga, T. (J. R. Soc., Interface, 2008)

(untitled) - Blakemore, R. P. (Annu. Rev. Microbiol., 1982)

(untitled) - Thornhill, R. H.; Burgess, J. G.; Matsunaga, T. (Appl. Environ. Microbiol., 1995)

(untitled) - Spring, S.; Schleifer, K.-H. (Syst. Appl. Microbiol., 1995)

(untitled) - Hosea, M.; Greene, B.; Mcpherson, R.; Henzl, M.; Alexander, M. D.; Darnall, D. W. (Inorg. Chim. Acta, 1986)

(untitled) - Scarano, G.; Morelli, E. (Plant Sci., 2003)

(untitled) - Krumov, N.; Perner-Nochta, I.; Oder, S.; Gotcheva, V.; Angelov, A.; Posten, C. (Chem. Eng. Technol., 2009)

(untitled) - Sastry, M.; Ahmad, A.; Khan, M. I.; Kumar, R. (Curr. Sci., 2003)

(untitled) - Mukherjee, P.; Senapati, S.; Mandal, D.; Ahmad, A.; Khan, M. I.; Kumar, R.; Sastry, M. (ChemBioChem, 2002)

(untitled) - Ahmad, A.; Mukherjee, P.; Senapati, S.; Mandal, D.; Khan, M. I.; Kumar, R.; Sastry, M. (Colloids Surf., B, 2003)

(untitled) - Ahmad, A.; Mukherjee, P.; Mandal, D.; Senapati, S.; Khan, M. I.; Kumar, R.; Sastry, M. (J. Am. Ceram. Soc., 2002)

(untitled) - Bansal, V.; Rautaray, D.; Ahmad, A.; Sastry, M. (J. Mater. Chem., 2004)

(untitled) - Reese, R.; Winge, D. R. (Int. J. Biol. Chem., 1988)

(untitled) - Dameron, C. T.; Reese, R. N.; Mehra, R. K.; Kortan, A. R.; Carroll, P. J.; Steigerwald, M. L.; Brus, L. E.; Winge, D. R. (Nature, 1989)

(untitled) - Kowshik, M.; Vogel, W.; Urban, J.; Kulkarni, S. K.; Paknikar, K. M. (Adv. Mater., 2002)

(untitled) - Kowshik, M.; Ashtaputre, S.; Kharrazi, S.; Vogel, W.; Urban, J.; Kulkarni, S. K.; Paknikar, K. M. (Nanotechnology, 2002)

(untitled) - Fricker, M.; Ågren, J.; Segerman, B.; Knutsson, R.; Ehling-Schulz, M. (Int. J. Food Microbiol., 2011)

(untitled) - Tripathi, D. K.; Tripathi, A.; Shweta, S.; ingh, S.; Singh, Y.; Vishwakarma, K.; Yadav, G.; Sharma, S.; Singh, V. K.; Mishra, R. K.; Upadhyay, R. G.; Dubey, N. K.; et al. (Front. Microbiol., 2017)

(untitled) - Fahmy, H. M.; Saad, O. A.; Rashed, H. A.; Hessen, O. E. A.; Elgamal, K. H. I.; Aboelfetouh, M. M. (J. Bionanosci., 2017)

(untitled) - Mitiku, A. A.; Yilma, B. (Int. J. Pharm. Sci. Rev. Res., 2017)

(untitled) - Rajeshkumar, S.; Bharath, L. V. (Chem.-Biol. Interact., 2017)

(untitled) - Salvadori, M. R.; Ando, R. A.; do Nascimento, C. A. O.; Corrêa, B. (PLoS One, 2014)

(untitled) - Salvadori, M. R.; Ando, R. A.; Nascimento, C. A. O.; Corrêa, B. (PLoS One, 2015)

The nanoscience and technology of renewable biomaterials - Lucia, L. A.; Rojas, O. (John Wiley & Sons, Inc., 2009)

(untitled) - Mohammadinejad, R.; Karimi, S.; Iravani, S.; Varma, R. S. (Green Chem., 2016)

(untitled) - Gorb, E.; Haas, K.; Henrich, A.; Enders, S.; Barbakadze, N.; Gorb, S. (J. Exp. Biol., 2005)

(untitled) - Bargel, H.; Koch, K.; Cerman, Z.; Neinhuis, C. (Funct. Plant Biol., 2006)

Plant cuticles: an integrated functional approach - Barnes, J.; Cardoso Velhena, J. (BIOS Scientific Publishers Ltd., 1996)

Biology of the plant cuticle - Pfündel, E. E.; Agati, G.; Cerovic, G. Z. (Optical properties of plant surfaces, 2008)

(untitled) - Barthlott, W.; Neinhuis, C. (Planta, 1997)

(untitled) - Nguyen, S. H.; Webb, H. K.; Mahon, P. J.; Crawford, R. J.; Ivanova, E. P. (Molecules, 2014)

(untitled) - Xue, Y.; Lv, P.; Lin, H.; Duan, H. (Appl. Mech. Rev., 2016)

(untitled) - Zhang, Y.-L.; Xia, H.; Kim, E.; Sun, H.-B. (Soft Matter, 2012)

Fundamentals of microfabrication: the science of miniaturization - Madou, M. J. (CRC Press, 2002)

(untitled) - Ming, W.; Wu, D.; van Benthem, R.; De With, G. (Nano Lett., 2005)

(untitled) - Chow, T. S. (Nanotechnology, 2007)

(untitled) - Roach, P.; Shirtcliffe, N. J.; Newton, M. I. (Soft Matter, 2008)

(untitled) - Koch, K.; Barthlott, W. (Philos. Trans. R. Soc., A, 2009)

(untitled) - Cong, H.-P.; Ren, X.-C.; Wang, P.; Yu, S.-H. (ACS Nano, 2012)

(untitled) - Nguyen, D. D.; Tai, N.-H.; Lee, S.-B.; Kuo, W.-S. (Energy Environ. Sci., 2012)

(untitled) - Rafiee, J.; Rafiee, M. A.; Yu, Z.-Z.; Koratkar, N. (Adv. Mater., 2010)

(untitled) - Zhang, X.; Wan, S.; Pu, J.; Wang, L.; Liu, X. (J. Mater. Chem., 2011)

(untitled) - Zang, J.; Ryu, S.; Pugno, N.; Wang, Q.; Tu, Q.; Buehler, M. J.; Zhao, X. (Nat. Mater., 2013)

(untitled) - Dong, J.; Yao, Z.; Yang, T.; Jiang, L.; Shen, C. (Sci. Rep., 2013)

(untitled) - Lee, J.-S.; Yoon, J.-C.; Jang, J.-H. (J. Mater. Chem. A, 2013)

(untitled) - Wang, J.-N.; Zhang, Y.-L.; Liu, Y.; Zheng, W.; Lee, L. P.; Sun, H.-B. (Nanoscale, 2015)

(untitled) - Feng, L.; Li, S.; Li, Y.; Li, H.; Zhang, L.; Zhai, J.; Song, Y.; Liu, B.; Jiang, L.; Zhu, D. (Adv. Mater., 2002)

(untitled) - Feng, L.; Zhang, Y.; Xi, J.; Zhu, Y.; Wang, N.; Xia, F.; Jiang, L. (Langmuir, 2008)

(untitled) - Wootton, R. J. (Annu. Rev. Entomol., 1992)

(untitled) - Moussian, B. (Insect Biochem. Mol. Biol., 2010)

(untitled) - Kreuz, P.; Arnold, W.; Kesel, A. B. (Ann. Biomed. Eng., 2001)

(untitled) - Gorb, S. N. (Naturwissenschaften, 1999)

(untitled) - Hu, H.-M. S.; Watson, G. S.; Cribb, B. W.; Watson, J. A. (J. Exp. Biol., 2011)

(untitled) - Ditsche-Kuru, P.; Barthlott, W.; Koop, J. H. E. (Zoology (Munich, Ger.), 2012)

(untitled) - Neville, A.; Parry, D.; Woodhead-Galloway, J. (J. Cell Sci., 1976)

(untitled) - Dirks, J.-H.; Taylor, D. (J. Exp. Biol., 2012)

(untitled) - Howard, R. W.; Blomquist, G. J. (Annu. Rev. Entomol., 2005)

(untitled) - Kramer, K. J.; Muthukrishnan, S. (Insect Biochem. Mol. Biol., 1997)

(untitled) - Watson, G. S.; Cribb, B. W.; Watson, J. A. (ACS Nano, 2010)

(untitled) - Byun, D.; Hong, J.; Saputra; Ko, J. H.; Lee, Y. J.; Park, H. C.; Byun, B.-K.; Lukes, J. R. (J. Bionic Eng., 2009)

(untitled) - Watson, G. S.; Cribb, B. W.; Watson, J. A. (PLoS One, 2011)

(untitled) - Sun, M.; Watson, G. S.; Zheng, Y.; Watson, J. A.; Liang, A. (J. Exp. Biol., 2009)

(untitled) - Sun, M.; Liang, A.; Watson, G. S.; Watson, J. A.; Zheng, Y.; Jiang, L. (PLoS One, 2012)

(untitled) - Plattner, L. (J. R. Soc., Interface, 2004)

(untitled) - Boulenguez, J.; Berthier, S.; Leroy, F. (Appl. Phys. A, 2012)

(untitled) - Gillett, J. D.; Wigglesworth, V. B. (Proc. R. Soc. London, Ser. B, 1932)

(untitled) - Stork, N. (J. Exp. Biol., 1980)

(untitled) - Autumn, K.; Liang, Y. A.; Hsieh, S. T.; Zesch, W.; Chan, W. P.; Kenny, T. W.; Fearing, R.; Full, R. J. (Nature, 2000)

(untitled) - Bauchhenß, E. (Z. Morphol. Tiere, 1979)

(untitled) - Walker, G.; Yulf, A. B.; Ratcliffe, J. (J. Zool., 1985)

(untitled) - Gorb, S. N. (J. Insect Physiol., 1998)

(untitled) - Homann, H. (Naturwissenschaften, 1957)

(untitled) - Hiller, U. (Z. Morphol. Tiere, 1968)

(untitled) - Autumn, K.; Sitti, M.; Liang, Y. A.; Peattie, A. M.; Hansen, W. R.; Sponberg, S.; Kenny, T. W.; Fearing, R.; Israelachvili, J. N.; Full, R. J. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Arzt, E.; Enders, S.; Gorb, S. (Z. Metallkd., 2002)

(untitled) - Arzt, E.; Gorb, S.; Spolenak, R. (Proc. Natl. Acad. Sci. U. S. A., 2003)

(untitled) - Bruet, B. J. F.; Qi, H. J.; Boyce, M. C.; Panas, R.; Tai, K.; Frick, L.; Ortiz, C. (J. Mater. Res., 2005)

Nanomonde: des nanosciences aux nanotechnologies - Moret, R. (CNRS Éditions, 2006)

(untitled) - Freeman, C. L.; Harding, J. H.; Quigley, D.; Rodger, P. M. (Angew. Chem., Int. Ed., 2010)

(untitled) - Gong, T.; Xie, J.; Liao, J.; Zhang, T.; Lin, S.; Lin, Y. (Bone Res., 2015)

(untitled) - Papazoglou, E. S.; Parthasarathy, A. (Synth. Lect. Biomed. Eng., 2007)

DNA structure and function - Sinden, R. R. (Academic Press, Inc., 2012)

Cell biology by the numbers - Milo, R.; Phillips, R. (Garland Science, 2015)

(untitled) - Ménétret, J.-F.; Schaletzky, J.; Clemons, W. M., Jr; Osborne, A. R.; Skånland, S. S.; Denison, C.; Gygi, S. P.; Kirkpatrick, D. S.; Park, E.; Ludtke, S. J.; Rapoport, T. A.; Akey, C. W. (Mol. Cell, 2007)

Nanoscience: the science of the small in physics, engineering, chemistry, biology and medicine - Schaefer, H.-E. (Springer Science & Business Media, 2010)

(untitled) - Li, X.; Wang, L.; Fan, Y.; Feng, Q.; Cui, F.-Z.; Watari, F. (J. Biomed. Mater. Res., Part A, 2013)

(untitled) - Robling, A. G.; Stout, S. D. (Cells Tissues Organs, 1999)

(untitled) - Faingold, A.; Cohen, S. R.; Reznikov, N.; Wagner, H. D. (Acta Biomater., 2013)

(untitled) - Liu, H.; Yazici, H.; Ergun, C.; Webster, T. J.; Bermek, H. (Acta Biomater., 2008)

(untitled) - Discher, D. E.; Mooney, D. J.; Zandstra, P. W. (Science, 2009)

(untitled) - Gong, T.; Xie, J.; Liao, J.; Zhang, T.; Lin, S.; Lin, Y. (Bone Res., 2015)

(untitled) - Odde, D. (Cell, 2011)

Lehninger principles of biochemistry - Nelson, D. L.; Lehninger, A. L.; Cox, M. M. (Macmillan, 2008)

DNA-Templated Nanomaterials - Becerril-Garcia, H. A. (Brigham Young University, 2007)

(untitled) - Crick, F. H. C. (Science, 1963)

(untitled) - Watson, J. D. (Science, 1963)

(untitled) - Dickerson, R. E.; Drew, H. R.; Conner, B. N.; Wing, R. M.; Fratini, A. V.; Kopka, M. L. (Science, 1982)

Nucleic Acid Research - Dickerson, R. E.; Conner, B. N.; Kopka, M. L.; Drew, H. R. (The Geometry of A, B, and Z DNA, 1983)

(untitled) - Petty, J. T.; Zheng, J.; Hud, N. V.; Dickson, R. M. (J. Am. Ceram. Soc., 2004)

(untitled) - Lin, C.; Jungmann, R.; Leifer, A. M.; Li, C.; Levner, D.; Church, G. M.; Shih, W. M.; Yin, P. (Nat. Chem., 2012)

(untitled) - Chen, W.-Y.; Lan, G.-Y.; Chang, H.-T. (Anal. Chem., 2011)

(untitled) - Samanta, A.; Medintz, I. L. (Nanoscale, 2016)

(untitled) - Pinheiro, A. V.; Han, D.; Shih, W. M.; Yan, H. (Nat. Nanotechnol., 2011)

(untitled) - Lin, C.; Liu, Y.; Yan, H. (Biochemistry, 2009)

(untitled) - Zhang, D. Y.; Seelig, G. (Nat. Chem., 2011)

(untitled) - Lo, P. K.; Metera, K. L.; Sleiman, H. F. (Curr. Opin. Chem. Biol., 2010)

(untitled) - Jones, M. R.; Seeman, N. C.; Mirkin, C. A. (Science, 2015)

(untitled) - Fernandes, F. M.; Coradin, T.; Aimé, C. (Nanomaterials, 2014)

(untitled) - Wang, L.; Sun, Y.; Li, Z.; Wu, A.; Wei, G. (Materials, 2016)

(untitled) - Breslow, R.; Overman, L. E. (J. Am. Ceram. Soc., 1970)

Artificial enzymes - Breslow, R. (John Wiley & Sons, Inc., 2006)

From enzyme models to model enzymes - Kirby, A. J.; Hollfelder, F. (Royal Society of Chemistry, 2009)

(untitled) - Wei, H.; Wang, E. (Chem. Soc. Rev., 2013)

(untitled) - Pavlov, V.; Xiao, Y.; Shlyahovsky, B.; Willner, I. (J. Am. Ceram. Soc., 2004)

(untitled) - Leggett, R.; Lee-Smith, E. E.; Jickells, S. M.; Russell, D. A. (Angew. Chem., 2007)

(untitled) - Hawkins, M. J.; Soon-Shiong, P.; Desai, N. (Adv. Drug Delivery Rev., 2008)

(untitled) - Ryan, S.; Kell, A. J.; van Faassen, H.; Tay, L.-L.; Simard, B.; MacKenzie, R.; Gilbert, M.; Tanha, J. (Bioconjugate Chem., 2009)

(untitled) - Jeevanandam, J.; San Chan, Y.; Danquah, M. K. (Biochimie, 2016)

(untitled) - Kennedy, A. J.; Hull, M. S.; Steevens, J. A.; Dontsova, K. M.; Chappell, M. A.; Gunter, J. C.; Weiss, C. A., Jr (Environ. Toxicol. Chem., 2008)

(untitled) - Wang, Y.; Li, Y.; Pennell, K. D. (Environ. Toxicol. Chem., 2008)

(untitled) - Tervonen, T.; Linkov, I.; Figueira, J. R.; Steevens, J.; Chappell, M.; Merad, M. (J. Nanopart. Res., 2009)

(untitled) - Bortoleto, G. G.; de Oliveira Borges, S. S.; Bueno, M. I. M. S. (Anal. Chim. Acta, 2007)

(untitled) - Chen, Q.; Saltiel, C.; Manickavasagam, S.; Schadler, L. S.; Siegel, R. W.; Yang, H. (J. Colloid Interface Sci., 2004)

(untitled) - Gnach, A.; Lipinski, T.; Bednarkiewicz, A.; Rybka, J.; Capobianco, J. A. (Chem. Soc. Rev., 2015)

(untitled) - Xia, T.; Kovochich, M.; Brant, J.; Hotze, M.; Sempf, J.; Oberley, T.; Sioutas, C.; Yeh, J. I.; Wiesner, M. R.; Nel, A. E. (Nano Lett., 2006)

(untitled) - Ivask, A.; Kurvet, I.; Kasemets, K.; Blinova, I.; Aruoja, V.; Suppi, S.; Vija, H.; Käkinen, A.; Titma, T.; Heinlaan, M. (PLoS One, 2014)

(untitled) - Lippmann, M. (Environ. Health Perspect., 1990)

(untitled) - Gurr, J.-R.; Wang, A. S. S.; Chen, C.-H.; Jan, K.-Y. (Toxicology, 2005)

(untitled) - Oberdörster, G.; Oberdörster, E.; Oberdörster, J. (Environ. Health Perspect., 2005)

(untitled) - Sayes, C. M.; Fortner, J. D.; Guo, W.; Lyon, D.; Boyd, A. M.; Ausman, K. D.; Tao, Y. J.; Sitharaman, B.; Wilson, L. J.; Hughes, J. B.; West, J. L.; Colvin, V. L. (Nano Lett., 2004)

(untitled) - Johnston, C. J.; Finkelstein, J. N.; Mercer, P.; Corson, N.; Gelein, R.; Oberdörster, G. (Toxicol. Appl. Pharmacol., 2000)

(untitled) - D'Silva, J.; van Calster, G. (Eur. J. Health Law, 2009)

(untitled) - Marchant, G. E.; Sylvester, D. J.; Abbott, K. W.; Danforth, T. L. (Stud. Ethics Law Technol., 2009)

Nanomaterials (2012)

Scientific committee on emerging and newly identified health risks SCENIHR, Risk Assessment of Products of Nanotechnologies (2009)

(untitled) - Ajazzuddin, M.; Jeswani, G.; Kumar Jha, A. (Recent Pat. Nanomed., 2015)

(untitled) - Johnson, V. R. (Penn St. L. Rev., 2016)

(untitled) - Thomas, T.; Thomas, K.; Sadrieh, N.; Savage, N.; Adair, P.; Bronaugh, R. (Toxicol. Sci., 2006)

Principles for the Oversight of Nanotechnologies and Nanomaterials (2007)

Nanomaterial fact sheet (2015)

Soil Association bans nanomaterials from organic products (The Guardian, 2008)

Nanotechnology prohibited from Australian certified organic beauty products (2012)

(untitled) - Roseboro, K. (Org. Non-GMO Rep., 2010)